7(x-4)=3x+9

Simple and best practice solution for 7(x-4)=3x+9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(x-4)=3x+9 equation:



7(x-4)=3x+9
We move all terms to the left:
7(x-4)-(3x+9)=0
We multiply parentheses
7x-(3x+9)-28=0
We get rid of parentheses
7x-3x-9-28=0
We add all the numbers together, and all the variables
4x-37=0
We move all terms containing x to the left, all other terms to the right
4x=37
x=37/4
x=9+1/4

See similar equations:

| 7x-8+78=180 | | 7x-3(4x+8)=36 | | 2+2x6=14 | | 1. 2x+5+65=180 | | 4^(x-3)=250 | | 0.5(5x+1)=3 | | 1/5x+4/5x=13 | | 9687=22/7d | | 1/2a+3/5=a+5 | | x+55+86+7x-58+9x-38+3x+47+x+50=360 | | 4x-36=3x/6 | | (7m-8)=(3m+6) | | 3x-10=-15 | | 0=a^2-4a+29 | | 8-3*(x)=18-x | | d/14-8=5 | | x^2-22x5-252=0 | | 4n^2-24n-28=0 | | 35-14(x)=9-(x) | | -5x+-15=-20 | | u2–34u=0 | | x^2-22x-252=0 | | 2(2x+2)=2x-2-x | | 51=-7t-5 | | 6/3=3x/3 | | 78+n/7=64 | | 3(2x+5)=4x-7 | | z/7+5=-56 | | 9x–(2x+5)= | | k/3+7=38 | | 9x–(2x+5)=4(5x+2) | | 5x+8+3x+4=-40-4 |

Equations solver categories